Mitigation of Cyclone Disaster in S.P.S. Nellore District, Andhra Pradesh using GIS - Chendrayudu, N.; Reddy, D. Chandrasekhar; Krishnaiah, K.; Penchalaiah, T. (National Geographical Journal of India, 2022)
Not available